An evaluation of German active labor market policies and its entrepreneurship promotion - Moritz Zöllner; Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2016)
This paper reviews the results of studies that investigate the most important active labour market policy (ALMP) measures in Germany. A particular focus is on programs devoted to foster entrepreneurship which can make important contributions to a country's growth and social welfare. The available evidence suggests that most ALMP measures increase labour market prospects of the participants. Evaluations of the entrepreneurship promotion activities show high success rates as well as high cost efficiency. The bulk share of participants of entrepreneurship measures is still self-employed after several years and nearly one third of these businesses had at least one employee. We mention problems regarding the evaluation of previous programs and highlight future challenges of German ALMP.
Keywords: J08; J64; J68; L26; 330; Active labour market policy; evaluations; effectiveness; entrepreneurship